A Study on Prognostic Factors in Management of Breast Carcinoma in A Tertiary Care Hospital - Sivaramakrishna Valluru; C Srikanth Reddy; Shanmukha Srinivasulu Udayagiri; Sada Surya Vidavaluru (Krupanidhi College of Pharmacy, 2023)
Breast cancer is the most common malignant tumor and leading cause of death in women worldwide. It accounts for 15% of all cancer deaths According to World Health Organisation (WHO), approximately 70% of breast malignancies occur in women with unknown risk factorsThe prognostic factor can be defined as a measurable variable which correlates with natural history of the disease. The most significant factor which influences prognosis in breast cancer is axillary lymph node involvement, which is usually assessed at time of surgery using sentinel lymph node biopsy or axillary lymph node dissection. The number of lymph nodal involvement is also significant. Involvement of 1-3 lymph nodes carry better prognosis than 4-9 and more than 9 lymph nodes involvement. Size of the tumour has long been recognized as a prognostic factor and as predictor of axillary node status, with larger tumours being associated with a bad prognosis and an increased incidence of nodal metastasis. This study is conducted in Department of General Surgery, SVRRGGH, Sri Venkateswara Medical College, Tirupati for a period of more than one and half year after getting approval from Institutional Ethical Committee on March 2021. A prospective study of 50 patients who fulfilled Inclusion Criteria is taken into consideration to know how prognostic factors like tumor size & grade, axillary lymphnode involvement are influencing the prognosis and management of breast carcinoma. Patients who took part in the study were from 28-68 years of age. Majority of people were in the age group of 46-55 years (38%). Increasing age, involvement of axillary lymph nodes, tumors with larger size and higher grade, and lymphovascular invasions are all associated with worse prognosis Keywords: Estrogen Receptor, Progesterone Receptor, Locally Advanced Breast Carcinoma